The Relationship Between Leg Muscle Power And Waist Flexion On Sickle Kick Ability In Male Students Of Pencak Silat Extracurricular SMAN 1 Terusan Nunyai Central Lampung Regency - Dian Musrianto; Lungit Wicaksono; Joan Siswoyo; Heru Sulistianta (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to find out how much of a relationship between leg muscle power and waist flexibility on the ability to kick a sickle in pencak silat extracurricular male students at SMA Negeri 1 Terusan Nunyai. This study uses a quantitative method with a correlational design. Data was collected through the standing long jump test, the sit and reach test, and the sickle kick test. The research sample consisted of 20 male students. The data analysis technique used in this study is statistics through SPSS 23 application correlation. The results showed a significant relationship between leg muscle power of 0.528 > R table 0.443, and waist flexibility of 0.341 < R table 0.443, with sickle kick ability of 0.623 > R table 0.443. Both free variables contribute significantly to improved sickle kick performance.